Application of Learning Model: Problem-based Learning to Increase Learning Outcomes in Budget Plan Subject - Wardhana Rizqi Aminulloh; Heri Suryaman (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2022)
This study aims to describe instrument validity, learning outcomes using conventional learning models, learning outcomes using Problem Based Learning models, and differences in learning outcomes between the two learning models on the subject of Budget Plan at SMKN 1 Glagah Banyuwangi. This type of research is quantitative with a quasi-experimental method. The experimental design refers to the Non-equivalent Control Group Design model. The sample involved was 60 students taken from class XI DPIB SMKN 1 Glagah Banyuwangi and divided into 2 classes, namely the experimental and control classes. The number of students per class is 30 students. Data collection in this study was carried out through instrument validation questionnaires and post-tests. Data analysis was carried out through normality test as a prerequisite test and paired samples test as hypothesis testing. This study shows the results in the form of the validity of the instruments used, which are in very good agreement with the syllabus validation of 87%, lesson plans of 85%, and post-test questions of 85%. The learning outcomes of the control class were categorized with an average of 84.33, while the experimental class was 90 which was included in the good category. The application of the Problem Based Learning learning model that was carried out in the experimental class got a higher score with a difference of 5.67. Paired samples test through SPSS software showed a significance result of 0.002 or less than 0.005. Based on the results of hypothesis testing, it can be concluded that Ha is accepted which indicates a significant influence between the implementation of Problem Based Learning and conventional learning